Optimization of Antioxidant Potential of Penicillium granulatum Bainier by Statistical Approaches. (15th May 2012) - Chandra, Priyanka; Arora, Daljit Singh
Abstract : A three-step optimization strategy which includes one-factor-at-a-time classical method and different statistical approaches (Plackett-Burman design and response surface methodology) that were applied to optimize the antioxidant potential of Penicillium granulatum. Antioxidant activity was assayed by different procedures and compared with total phenolic content. Primarily, different carbon and nitrogen sources were screened by classical methods, which revealed sucrose and NaNO3 to be the most suitable. In second step, Plackett-Burman design also supported sucrose and NaNO3 to be the most significant. In third step, response surface analysis showed 4.5% sucrose, 0.1% NaNO3, and incubation temperature of 25°C to be the optimal conditions. Under these conditions, the antioxidant potential assayed through different procedures was 78.2%, 70.1%, and 78.9% scavenging effect for DPPH radical, ferrous ion, and nitric oxide ion, respectively. The reducing power showed an absorbance of 1.6 with 68.5% activity for FRAP assay.